2023
DOI: 10.32583/keperawatan.v15i2.851
|View full text |Cite
|
Sign up to set email alerts
|

Faktor yang Berhubungan dengan Tingkat Stres pada Ibu Hamil dalam Menghadapi Persalinan

Abstract: Kehamilan dapat menimbulkan suatu krisis maturitas yang dapat menyebabkan stres. Stres pada ibu hamil memiliki keterkaitan dalam menimbulkan stres saat hamil, melahirkan dan nifas. Tujuan penelitian ini untuk melihat faktor -faktor yang berhubungan dengan tingkat stress pada ibu hamil dalam menghadapi persalinan. Jenis penelitian survei analitik dengan pendekatan cross sectional yang dilakukan di Wilayah Kerja Puskesmas Lubuk Buaya tanggal 25 April-7 Mei 2022. Populasi adalah semua ibu hamil yang berkunjung ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…This research supports Yazia and Hamdayani (2020) where there is a significant relationship between socio-economic level and the level of anxiety in mothers when facing menopause. The results of this study also support the results of previous research by Rostina (2009) showing that there is a socioeconomic relationship with premenopausal mothers' anxiety in facing menopause.…”
Section: Relationship Between Income and Anxiety During Menopausesupporting
confidence: 79%
See 1 more Smart Citation
“…This research supports Yazia and Hamdayani (2020) where there is a significant relationship between socio-economic level and the level of anxiety in mothers when facing menopause. The results of this study also support the results of previous research by Rostina (2009) showing that there is a socioeconomic relationship with premenopausal mothers' anxiety in facing menopause.…”
Section: Relationship Between Income and Anxiety During Menopausesupporting
confidence: 79%
“…Other research also found that there was no relationship between education level and anxiety (Anggraeni, 2022). Research is inversely proportional to Yazia and Hamdayani (2020) that there is a relationship between education and anxiety.…”
Section: The Relationship Between Education and Anxiety During Menopausementioning
confidence: 99%
“…Masalah pekerjaan seorang wanita dalam masa menopause berkaitan pada pemenuhan kebutuhan hidup keseharian, misalnya pangan, sandang, kesehatan, perumahan, sosial dan rekreasi. Dari keadaan psikis dan fisik yang rendah 79 karena ibu menopause tidak bisa bekerja secara maksimal (Yazia & Hamdayani, 2020).…”
Section: Pada Temuanunclassified
“…Menurut penelitian Yazia & Hamdayani (2020) dengan ekonomi yang rendah atau cukup, ibu menopause bisa memberikan pemenuh pada beberapa kebutuhan hidup mereka, khususnya pada kebutuhan seperti pelayanan Kesehatan.…”
Section: Pada Temuanunclassified
See 1 more Smart Citation